Pilot Study of Ofloxacin and Interferon-Alpha Combination Therapy for Chronic Hepatitis C without Sustained Response to Initial Interferon Therapy - Masafumi Komatsu; Tohru Ishii; Tsuyoshi Ono; Takao Hoshino; Tomoyuki Kuramitsu; Takashi Goto; Tomoo Fujii; Itaru Toyoshima; Mitsuro Chiba; Osamu Masamune (Canadian Journal of Gastroenterology)
A controlled trial comparing combination therapy with ofloxacin (OFLX) and interferon (IFN) versus IFN monotherapy was conducted in patients with chronic hepatitis C who failed IFN therapy. Twenty patients were assigned randomly to two groups. Equal doses of recombinant IFNα-2b were administered to each group for 24 weeks. For the IFN plus OFLX group, OFLX was administered for 12 weeks at a daily dose of 600 mg. Levels of hepatitis C virus RNA declined significantly from the first month after the start of IFN treatment compared with those before administration in both groups. Serum alanine aminotransferase levels were significantly lower in the IFN plus OFLX group at two and six months after the start of treatment than levels in the IFN group. The fraction of subjects whose levels of serum ALT normalized was also higher in the IFN plus OFLX group. Larger clinical trials should be undertaken.